Information Management and Mediation in a Digital Reference Service Focused in Social Sciences - Corda, María Cecilia (BJIS.)
This paper investigates the current relationship between information management and information mediation along with the digital reference service through a case study which took place in an academic library. The concept of information mediation is herein analyzed, since a conceptual examination provides elements that will help people to comprehend and evaluate the concerned service. The information professional plays a very important role in the mediation aforementioned, which may be directly or indirectly; consciously or unconsciously; by himself/herself or plurally; individually or inserted into a group ? in all such manners that mediator facilitates the acquisition of information, fully or partially satisfying a user?s need of all sorts of knowledge. Meanwhile, we here approach information management from a scope that points out a description over performed activities concerned to policies and procedures put into effect until the service evaluation by proposing a criterion for such point. Finally, we outline a few actions to be implemented in long-term perspective, which goal is to continually ameliorate such assistance, taking in account the human factor